2009
DOI: 10.1021/es900070h
|View full text |Cite
|
Sign up to set email alerts
|

Fate of Carbamazepine during Water Treatment

Abstract: Seven transformation products of carbamazepine generated by at least one of three common water treatment technologies (UV-radiation, oxidation with chlorine dioxide (ClO2), and biological treatment with activated sludge) were identified by complementary use of ion trap, single quadrupole, and quadrupole-time-of-flight mass spectrometers. Acridine was formed during all of the three treatment processes, while acridine 9-carbaldehyde was identified as an intermediate during ClO2 oxidation. Further treatment of ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
91
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 213 publications
(95 citation statements)
references
References 28 publications
4
91
0
Order By: Relevance
“…It is assumed that removal of carbamazepine from surface waters will occur largely via the photodegradation pathway as sorption of carbamazepine is very limited (Ternes et al, 2002;Scheytt et al, 2005;Clara et al, 2004) and it is resistant to biodegradation (Clara et al, 2004;Kosjek et al, 2009). Hence, the formation of stable photodegradation products is not only relevant to wastewater treatment processes, where UV treatment may be implemented to assist with microbial disinfection (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is assumed that removal of carbamazepine from surface waters will occur largely via the photodegradation pathway as sorption of carbamazepine is very limited (Ternes et al, 2002;Scheytt et al, 2005;Clara et al, 2004) and it is resistant to biodegradation (Clara et al, 2004;Kosjek et al, 2009). Hence, the formation of stable photodegradation products is not only relevant to wastewater treatment processes, where UV treatment may be implemented to assist with microbial disinfection (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Concentration profiles of the two transformation products were both below the detection limit after 120 minutes of UV treatment. Although methanol, a potential radical scavenger, was used as the solvent for the carbamazepine stock solution, Kosjek et al (2009) showed that the concentration of methanol used in this experiment should not have inhibited the decay of carbamazepine or the identified transformation products during treatment. Their investigation used the same benchtop UV-treatment system as the current experiment and showed no significant difference in carbamazepine decay in the presence of 1.2, 2.5 and 6.2 % methanol.…”
Section: Carbamazepine Uv Treatment Experimentsmentioning
confidence: 93%
See 1 more Smart Citation
“…A particular emphasis has been focused on pharmaceuticals with several reviews and studies dedicated to their degradation products in the environment (FattaKassinos et al, 2011a;Fatta-Kassinos et al, 2011b;Horvat et al, 2012) and in water treatment systems e.g. water works (Ternes et al, 2002;Kosjek and Heath, 2008;Kosjek et al, 2009). In these artificial systems biodegradation occurs concurrently with engineered processes like oxidation reactions with chlorine, chlorine dioxide, ozone and transformations by UV (Kosjek and Heath, 2008;Hollender et al, 2009;Kosjek et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…water works (Ternes et al, 2002;Kosjek and Heath, 2008;Kosjek et al, 2009). In these artificial systems biodegradation occurs concurrently with engineered processes like oxidation reactions with chlorine, chlorine dioxide, ozone and transformations by UV (Kosjek and Heath, 2008;Hollender et al, 2009;Kosjek et al, 2009). …”
Section: Introductionmentioning
confidence: 99%